An hydroxytyrosol enriched extract from olive mill wastewaters exerts antioxidant activity and antimicrobial activity on Pseudomonas savastanoi pv. savastanoi and Agrobacterium tumefaciens. Issue 16 (12th August 2021) - Pannucci, Elisa; Caracciolo, Rocco; Romani, Annalisa; Cacciola, Francesco; Dugo, Paola; Bernini, Roberta; Varvaro, Leonardo; Santi, Luca
Abstract: An hydroxytyrosol (HTyr) enriched extract (HTE), obtained from olive mill wastewaters (OMWW) through an eco-friendly, patented process was tested on two olive tree pathogens, Pseudomonas savastanoi pv. savastanoi (Pss) and Agrobacterium tumefaciens (At). Pss, in particular, is a feared treat for olive tree cultivation being the etiological agent of the olive knot disease responsible of severe production losses. Chemical characterization allowed to identify and quantify HTyr as the main constituent along with other low molecular weight phenols. HTE has proven potent antioxidant activity and significant antimicrobial activity against Pss and At in vitro, in both cases higher than hydroxytyrosol alone, suggesting an important role also of the minor phenolic components, which act synergistically with HTyr. Alternatives to the molecules currently present on the market are needed, but only the use of standardized extraction technologies would allow to conduct solid field studies and enable this circular approach to find a real application in the olive groves. Graphical Abstract: